A biomechanical study on the effect of lengthening magnitude on spine off-loading in magnetically controlled growing rod surgery: Implications on lengthening frequency. (16th September 2021) - Wong, Douglas C; Nafo, Wanis; Lu, William Weijia; Chee Cheung, Kenneth Man
Purpose: To assess whether the magnitude of lengthening in magnetically controlled growing rod (MCGR) surgeries has an immediate or delayed effect on spinal off-loading.Methods: 9 whole porcine spines were instrumented using two standard MCGRs from T9 to L5. Static compression testing using a mechanical testing system (MTS) was performed at three MCGR lengthening stages (0 mm, 2 mm, and 6 mm) in each spine. At each stage, five cycles of compression at 175N with 25 min of relaxation was carried out. Off-loading was derived by comparing the load sustained by the spine with force applied by the MTS to the spine. Micro-CT imaging was subsequently performed.Results: The mean load sustained by the vertebral body before lengthening was 39.69N, and immediately after lengthening was 25.12N and 19.91N at 2 mm and 6 mm lengthening, respectively; decreasing to 10.07N, 8.31N, and 8.17N after 25 minutes of relaxation, at 0 mm, 2 mm, and 6 mm lengthening stages, respectively. There was no significant difference in off-loading between 2 mm and 6 mm lengthening stages, either instantaneously ( p = 0.395) or after viscoelastic relaxation ( p = 0.958). CT images showed fractures/separations at the level of pedicle screws in six spines and in the vertebral body's growth zone in five spines after 6 mm MCGR lengthening.Conclusion: This study demonstrated MCGRs cause significant off-loading of the spine leading to stress shielding. 6 mm of lengthening caused tissue damage and microfractures in some spines. There was no significant difference in spine off-loading between 2 mm and 6 mm MCGR lengthening, either immediately after lengthening or after viscoelastic relaxation.